An unusual obstacle to the thoracic interlaminar epidural injection for the treatment of post-herpetic neuralgia - BİLİM, SERHAD; ŞENCAN, SAVAŞ; GÜNDÜZ, OSMAN HAKAN (My University, 2023)
Interlaminar epidural steroid injections corresponding to dermatomes affected by post-herpetic neuralgia (PHN) were found effective in reducing pain. Diffuse idiopathic skeletal hyperostosis (DISH) is a non-inflammatory condition that mainly occurs with calcification and ossification of spinal ligaments such as anterior and posterior longitudinal, interspinous, supraspinous ligament, and ligamentum flavum. In this case, it is presented that the failure of the access to the T7-T8 interlaminar space due to the supra/interspinous ligament calcification and ossification accompanied by thoracic DISH in a 73-year-old male for the treatment of PHN.

olduğu bulundu. Diffüz idiyopatik iskelet hiperostozu esas olarak anterior ve posterior longitudinal ligament, interspinöz, supraspinöz ligament ve ligamentum flavum gibi spinal ligamentlerin kalsifikasyonu ve kemikleşmesi ile ortaya çıkan inflamatuvar olmayan bir durumdur. Bu olguda, 73 yaşında postherpetik nevraljisi olan bir erkek hastada, torakal diffüz idiyopatik iskelet hiperostoza eşlik eden supra/interspinöz ligament kalsifikasyonu ve kemikleşme nedeniyle T7-T8 interlaminar epidural alana erişimin başarısız olma durumu sunuldu.
Postherpetik nevralji tedavisinde torasik interlaminar epidural enjeksiyonuna beklenmedik bir engel
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Diffuse idiopathic skeletal hyperostosis; epidural injection; pathologic calcification; postherpetic neuralgia; thoracic spondylosis; thoracic vertebrae; HERPES-ZOSTER; GABAPENTIN; SHINGLES; BLOCKS; Diffuse idiopathic skeletal hyperostosis; epidural injection; pathologic calcification; postherpetic neuralgia; thoracic spondylosis; thoracic vertebrae; Epidural Enjeksiyon; diffüz idiopatik iskelet hiperostozu; patolojik kalsifikasyon; postherpetik nevralji; torakal spondiloz; torakal vertebra